2022
DOI: 10.1371/journal.ppat.1010887
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of ApiAP2 protein DNA binding exhibit multistage activity against Plasmodium parasites

Abstract: Plasmodium parasites are reliant on the Apicomplexan AP2 (ApiAP2) transcription factor family to regulate gene expression programs. AP2 DNA binding domains have no homologs in the human or mosquito host genomes, making them potential antimalarial drug targets. Using an in-silico screen to dock thousands of small molecules into the crystal structure of the AP2-EXP (Pf3D7_1466400) AP2 domain (PDB:3IGM), we identified putative AP2-EXP interacting compounds. Four compounds were found to block DNA binding by AP2-EX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 90 publications
2
25
0
Order By: Relevance
“…Our AP2-LT ChIP-seq results identified an overlap with some AP2-EXP genome-wide binding sites, and previous work reported an overlap of AP2-I and AP2-EXP in vivo binding site preference 105 . Therefore, to expand the comparison to include all three factors, we identified the overlapping ChIP-seq peaks between AP2-LT (CACACA-binder), AP2-I (GTGCAC-binder), and AP2-EXP (TGCATGCA-binder) (Supplemental Figure 7D).…”
Section: Sequence Context Chromatin State and Timing Of Expression Di...supporting
confidence: 82%
See 2 more Smart Citations
“…Our AP2-LT ChIP-seq results identified an overlap with some AP2-EXP genome-wide binding sites, and previous work reported an overlap of AP2-I and AP2-EXP in vivo binding site preference 105 . Therefore, to expand the comparison to include all three factors, we identified the overlapping ChIP-seq peaks between AP2-LT (CACACA-binder), AP2-I (GTGCAC-binder), and AP2-EXP (TGCATGCA-binder) (Supplemental Figure 7D).…”
Section: Sequence Context Chromatin State and Timing Of Expression Di...supporting
confidence: 82%
“…In this context, we found several solutions including TFs that rely on sequence context to differentiate genome-wide binding site selection and others that are coordinated through changes in chromatin state features. Our findings are also relevant from a therapeutic perspective since ApiAP2 TFs are unique to plant and eukaryotic parasite genomes and have therefore been proposed as future antiparasitic drug targets 105,[111][112][113][114][115] .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Here we have begun unravelling one of the networks responsible for this process by placing the AP2XII-2-directed HDAC3/MORC complex above two genes that function in sexual stages, AP2X-10 and AAH1. In addition to utilizing a candidate-based approach as we have relied on for this study, the recent report highlighting inhibitors of AP2-family member activity may prove yet another tool for interrogating the role of AP2 factors in Toxoplasma developmental transitions (35).…”
Section: Resultsmentioning
confidence: 99%
“…AP2-SP is an ApiAP2 transcription factor with many target genes that are expressed specifically in the sporozoite stage of the Plasmodium life cycle (43,45,46). It has also been shown that disruption of this gene results in the loss of sporozoite formation entirely in the related P. berghei parasite and has important activities in blood stages in P. falciparum (43,(45)(46)(47). Another affected gene is pk4, which encodes an essential eIF2α kinase related enzyme and contains changes in its non-cytoplasmic domain as determined by InterPro domain predictions across 17X and 17XNL strains (48)(49)(50)(51).…”
Section: Variation Between the Py17xnl And Py17x Reference Genomes Pr...mentioning
confidence: 99%